"Everybody loves a redemption story around election time": Rob Ford and media construction of substance misuse and recovery - Kennedy, Liam (Canadian journal of criminology and criminal justice, 2017)
The crack cocaine scandal that embroiled former Toronto Mayor Rob Ford presents an opportunity to explore how we think and talk about substance (mis)use and recovery. Examining 1,836 articles from four Canadian newspapers, we analyze the ways news media frame Ford's use of crack cocaine. We find that Ford's drug use was often linked to a police investigation into gangs and guns, and much was made of his association with "Somali" drug dealers. Not only does this framing perpetuate prevailing stereotypes (crack cocaine use by racialized individuals living in poor and violent communities), but also it encourages the public to consider drugs a criminal justice issue and contributes to the stigma associated with drug use. Moreover, news media repeatedly suggested that Ford's problematic drug use could be solved ifhe took a leave from his job and entered a treatment facility. However, Ford's refusal to express shame and seek immediate treatment made him unworthy of compassion and instead rendered him deserving of censure. We argue that news media promoting a narrow pathway to addiction recovery and redemption ignores the realities of problematic drug use and justifies the continued marginalization of those who fail to meet this strict code of conduct.